SELECTION AND APPROBATION OF PRIORITY PROCESSING DIRECTIONS OF ORGANIC WASTE IN THE AGRARIAN SECTOR OF THE ECONOMY - Alexandr Gladilin; Lyudmila Kachanova (Вестник Северо-Кавказского федерального университета, 2022)
The article describes a methodology which has been developed for managing the selection ofpriority areas for processing organic wastes. Within the scope ofprocessing, a choice of technologies for the production of organic fertilizers has been made. The methodology includes a set of actions aimed at developing managerial decisions on the optimal use of available resources to achieve the set goals and which consists of three stages of implementation. The incoming and outgoing information of the implementation stages, as well as additional and clarifying criteria for each stage have been determined. The proposed methodology of managing the choice of priority areas for processing organic waste and fertilizer production technologies has been tested on the basis of the data from agricultural organizations in the Rostov Region. The indicators of economic efficiency, pointing at the prospects for implementing the direction of processing of organic waste by accelerated microbiological composting and its fertilizer production technologies have been determined. This direction of waste processing allows to reduce the cost of manufactured organic fertilizers, to increase the profitability of cultivation of crops when using fertilizers.